Desenvolvimento de uma fresadora CNC para produção de PCI controlada via Arduino nano - Soares, Jézzer Nathan (2021)
The aim of this paper consists in developing a CNC milling machine to manufacture printed circuit boards through a control platform and free software. To achieve it, first it will be elaborated a theoretical foundation to contribute to the comprehension of the several essential parts that will constitute the machine. To act as the processing unit of the milling machine, it was decided to utilize the Arduino Nano, a compact and complete version of the open-source platform Arduino. The milling machine will feature a system to provide the movement of the board in two horizontal coordinates (X and Y), while the structure that will bear the spindle motor, along with the tool that will remove the undesired material, be subjected to a vertical displacement (Z). Furthermore, based on easy accessibility, it was opted to utilize free and open-source software for the entire process of development of the boards, which are: KiCad, FlatCam, Candle, and GRBL.